2019
DOI: 10.3390/antibiotics8020080
|View full text |Cite
|
Sign up to set email alerts
|

Complement Evasion in Borrelia spirochetes: Mechanisms and Opportunities for Intervention

Abstract: Lyme disease (LD) is an increasingly prevalent, climate change-accelerated, vector-borne infectious disease with significant morbidity and cost in a proportion of patients who experience ongoing symptoms after antibiotic treatment, a condition known as post-treatment Lyme disease syndrome (PTLDS). Spirochetal bacteria of Borrelia species are the causative agents of LD. These obligate parasites have evolved sophisticated immune evasion mechanisms, including the ability to defeat the innate immune system’s compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Immune evasion strategies used by Borrelia to establish infection have been extensively reviewed elsewhere [35,[156][157][158][159][160][161][162][163]. Thus, the detailed biochemistry of host subversion is beyond the scope of this communication.…”
Section: Immune Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune evasion strategies used by Borrelia to establish infection have been extensively reviewed elsewhere [35,[156][157][158][159][160][161][162][163]. Thus, the detailed biochemistry of host subversion is beyond the scope of this communication.…”
Section: Immune Modulationmentioning
confidence: 99%
“…Subsequent work identified that OspC protects Borrelia from macrophage phagocytosis [134], although it is not yet known whether it functions as part of the IL-10 defense. Borrelia also has the capacity to resist the burst of reactive oxygen species produced by advancing phagocytes, via manganese superoxide dismutase antioxidation [163].…”
Section: Immune Modulationmentioning
confidence: 99%
“…The presence of both IgM and IgG antibodies was assessed, in order to identify recent or previous exposure to Borrelia species. Although antibody kinetics is unknown in sheep as in other animals, studies in humans revealed the presence of IgM antibodies at about 3 days after infection [44]. A weak antibody reaction was evidenced in a patient from the first day of infection in another study, which became stronger within a week [45].…”
Section: Discussionmentioning
confidence: 94%
“…The first line of defense implemented by the immune system to protect the host against pathogens is known as the complement system. The complement system is a tightly regulated cascade of enzymatic proteins responsible for the opsonization of pathogens, phagocytosis, cell lysis, and the establishment of the membrane attack complex (MAC) [ 6 , 7 ]. There are three main activation pathways: the classical pathway (CP), the alternative pathway (AP), and the lectin pathway (LP) ( Figure 1 ).…”
Section: Innate Responsementioning
confidence: 99%